Biallelic loss‐of‐function WNT5A mutations in an infant with severe and atypical manifestations of Robinow syndrome. Issue 4 (25th March 2018) - Birgmeier, Johannes; Esplin, Edward D.; Jagadeesh, Karthik A.; Guturu, Harendra; Wenger, Aaron M.; Chaib, Hassan; Buckingham, Julia A.; Bejerano, Gill; Bernstein, Jonathan A.
Abstract : Robinow syndrome (RS) is a well‐recognized Mendelian disorder known to demonstrate both autosomal dominant and autosomal recessive inheritance. Typical manifestations include short stature, characteristic facies, and skeletal anomalies. Recessive inheritance has been associated with mutations in ROR2 while dominant inheritance has been observed for mutations in WNT5A, DVL1, and DVL3 . Through trio whole genome sequencing, we identified a homozygous frameshifting single nucleotide deletion in WNT5A in a previously reported, deceased infant with a unique constellation of features comprising a 46, XY disorder of sex development with multiple congenital malformations including congenital diaphragmatic hernia, ambiguous genitalia, dysmorphic facies, shortened long bones, adactyly, and ventricular septal defect. The parents, who are both heterozygous for the deletion, appear clinically unaffected. In conjunction with published observations of Wnt5a double knockout mice, we provide evidence for the possibility of autosomal recessive inheritance in association with WNT5A loss‐of‐function mutations in RS.